Implementasi Nilai-Nilai Aksiologi Filsafat Pendidikan Islam dalam Pembentukan Akhlak Peserta Didik di SMP IT At-Taqwa Grabag Magelang - Ahmad Saad Nurifai; Mujiburrohman Mujiburrohman (TSAQOFAH, 2026)
The implementation of axiological values in Islamic educational philosophy has an important role in shaping students’ morals amid the challenges of social, cultural, and technological developments that influence the behavior of the younger generation. This study aims to analyze the implementation of axiological values in Islamic educational philosophy in shaping students’ morals at SMP IT At-Taqwa Grabag Magelang, identify the strategies used by the school, and examine their implications for strengthening students’ character. This study employed a qualitative approach with a case study design. Data were obtained through in-depth interviews, participatory observation, and documentation involving the principal, Islamic Religious Education teachers, homeroom teachers, and students. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was tested using source and technique triangulation. The results show that the implementation of axiological values in Islamic educational philosophy was carried out through the integration of Islamic values into learning, habituation of worship, teacher role modeling, strengthening of the school’s religious culture, and character development activities. The values developed include honesty, responsibility, discipline, social care, and religiosity. This implementation contributed to the formation of students’ morals as reflected in their daily behavior, both within and outside the school environment. The conclusion of this study emphasizes that the axiological values of Islamic educational philosophy have a strategic role in building students’ character and morals holistically. The implications of the study include theoretical contributions to the development of Islamic educational philosophy studies and practical implications for schools in strengthening an Islamic value-based religious culture as a foundation for sustainable character education.